WOVEN FABRICS COMPUTATIONAL SIMULATION USING BEAM-TO-BEAM CONTACTS FORMULATION - Saito, Mauro Takayama; Gay Neto, Alfredo (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
This paper presents the study of the woven fabric mechanical behavior using computational simulations. For that, the finite element analysis is used, where the woven weft and warps are modeled by three-dimensional beams and the interaction among them are performed by frictionless contact models. Therefore, the methodology for the woven fabrics computational simulation is developed, such as the constitution of these numerical models and computational tests techniques are presented. For it, super elliptical cross sections are considered for warp and weft textile fibers and the beam-to-beam contact formulations are assumed in the problem solution, where parametrized surfaces represent the boundaries of the beams that are candidate to contact. The result of the computational simulations is the possibility to study the textile mechanical behavior, where their properties can be obtained for woven fabrics samples under several load cases.